Effect of Dysglycemia on Urinary Lipid Mediator Profiles in Persons With Pulmonary Tuberculosis - Arriaga, María B.; Karim, Farina; Queiroz, Artur T.L.; Araújo-Pereira, Mariana; Barreto-Duarte, Beatriz; Sales, Caio; Moosa, Mahomed-Yunus S.; Mazibuko, Matilda; Milne, Ginger L.; Maruri, Fernanda; Serezani, Carlos Henrique; Koethe, John R.; et al. (Frontiers in Immunology, 2022)
Background: Oxidized lipid mediators such as eicosanoids play a central role in the inflammatory response associated with tuberculosis (TB) pathogenesis. Diabetes mellitus (DM) leads to marked changes in lipid mediators in persons with TB. However, the associations between diabetes-related changes in lipid mediators and clearance of M. tuberculosis (Mtb) among persons on anti-TB treatment (ATT) are unknown. Quantification of urinary eicosanoid metabolites can provide insights into the circulating lipid mediators involved in Mtb immune responses. Methods: We conducted a multi-site prospective observational study among adults with drug-sensitive pulmonary TB and controls without active TB; both groups had sub-groups with or without dysglycemia at baseline. Participants were enrolled from RePORT-Brazil (Salvador site) and RePORT-South Africa (Durban site) and stratified according to TB status and baseline glycated hemoglobin levels: a) TB-dysglycemia (n=69); b) TB-normoglycemia (n=64); c) non-TB/dysglycemia (n=31); d) non-TB/non-dysglycemia (n=29). We evaluated the following urinary eicosanoid metabolites: 11α-hydroxy-9,15-dioxo-2,3,4,5-tetranor-prostane-1,20-dioic acid (major urinary metabolite of prostaglandin E2, PGE-M), tetranor-PGE1 (metabolite of PGE2, TN-E), 9α-hydroxy-11,15-dioxo-2,3,4,5-tetranor-prostane-1,20-dioic acid (metabolite of PGD2, PGD-M), 11-dehydro-thromboxane B2 (11dTxB2), 2,3-dinor-6-keto-PGF1α (prostaglandin I metabolite, PGI-M), and leukotriene E4 (LTE4). Comparisons between the study groups were performed at three time points: before ATT and 2 and 6 months after initiating therapy. Results: PGE-M and LTE4 values were consistently higher at all three time-points in the TB-dysglycemia group compared to the other groups (p<0.001). In addition, there was a significant decrease in PGI-M and LTE4 levels from baseline to month 6 in the TB-dysglycemia and TB-normoglycemia groups. Finally, TB-dysglycemia was independently associated with increased concentrations of PGD-M, PGI-M, and LTE4 at baseline in a multivariable model adjusting for age, sex, BMI, and study site. These associations were not affected by HIV status. Conclusion: The urinary eicosanoid metabolite profile was associated with TB-dysglycemia before and during ATT. These observations can help identify the mechanisms involved in the pathogenesis of TB-dysglycemia, and potential biomarkers of TB treatment outcomes, including among persons with dysglycemia.